2019
DOI: 10.15244/pjoes/89575
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Degrading System of Phanerochaete chrysosporium and its Exploitation for Degradation of Synthetic Dyes Wastewater

Abstract: Azo dyes are the main group of dyes used in different industrial applications. These dyes are highly toxic for aquatic life, so their removal is of utmost importance before they can be disposed of in a main water body. The present study focused on degrading/mineralizing the synthetic reactive dye wastewater. Initial experiments were done with four indigenous white rot fungi. P. chrysosporium (PC) showed more potential toward degradation of synthetic dye wastewater than other three fungal strains, so it was sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Biosourced materials made of complex biopolymers such as lignocellulose or modified starch are biodegraded (composted) in a multi-step process. Initially, depolymerization takes place, i.e., enzymatic hydrolysis of cellulose or starch chains via, e.g., endoand exo-glucanases 53 and/or enzymatic oxidation of the lignin backbone via, e.g., manganese or lignin peroxidases 54,55 . Once the resulting oligomers, dimers, or monomers are released, they can be transported into the microorganisms 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosourced materials made of complex biopolymers such as lignocellulose or modified starch are biodegraded (composted) in a multi-step process. Initially, depolymerization takes place, i.e., enzymatic hydrolysis of cellulose or starch chains via, e.g., endoand exo-glucanases 53 and/or enzymatic oxidation of the lignin backbone via, e.g., manganese or lignin peroxidases 54,55 . Once the resulting oligomers, dimers, or monomers are released, they can be transported into the microorganisms 56 .…”
Section: Discussionmentioning
confidence: 99%
“…As Sepia Melanin is a heterogeneous substrate, we hypothesize that its biodegradation requires several types of extracellular enzymes to achieve complete biodegradation, via a mechanism very similar to the enzymatic oxidation of lignin, based on manganese peroxidase (Mn-P) and lignin peroxidase (Li-P) 54,68 . Moreover, a type of enzyme able to act on one type of eumelanin oligomer may have a different affinity towards different oligomers 33 , whereas a non-biodegraded oligomer will limit the exposure to extracellular enzymes of all the oligomers stacking beneath it.…”
Section: Discussionmentioning
confidence: 99%
“…They used an initial dye concentration of about 10-50 mg/l, compared to the RBBR concentration of 200 mg/l used in this study. Kiran et al (2019) found that when synthetic dye wastewater concentration was increased from 0.01-0.05%, the percent decolourization decreased from 80.93% to 24.705%. Taking into consideration these previous findings and the dye concentration, we can say that our isolates were more effective at dye decolorization.…”
Section: Dye Decolorization Studiesmentioning
confidence: 99%
“…Nevertheless, laccase enzymatic activity was never detected and a limited colour removal (10-11%) was evidenced. Kiran et al [64] investigated the colour removal performance of four P. chrysosporium strains on a dye wastewater solution prepared by mixing Reactive Blue, Reactive Violet and Reactive Yellow: after 6 day of incubation, the decolorization efficiency ranged from 38.9 to 82.9% depending on the tested strain and on the concentration of synthetic dyes, suggesting that larger quantity of the dye may cause a slower rate of dye removal; contrarily to results obtained in the present experimentation, laccase was always found in the range 5-25 IU mL -1 . This comparison suggests that P. chrysosporium was able to grow but not to synthetize the enzymatic activity requested for colour removal.…”
Section: Fungi Bioassaysmentioning
confidence: 99%